2020
DOI: 10.3390/ani10020204
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Race Intestinal Microbiota in Long-Distance Sled Dogs and Associations with Performance

Abstract: Simple Summary: The impact of the gut microbiota on endurance performance remains unresolved. Here, we present an association between endurance performance and gut microbiota dysbiosis in sled dogs. We present evidence that normobiosis-associated bacteria prevent the outgrowth of dysbiosis-associated bacteria during the race.Abstract: Although our understanding of the role of the gut microbiota in different diseases is improving, our knowledge regarding how the gut microbiota affects functioning in healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…This index achieved 74% sensitivity and 95% specificity for separation of healthy and CE dogs. Due to this good performance, numerous following studies utilized this index to quantify microbial dysbiosis for dogs or cats with CE ( 47 , 48 ), response to food ( 49 , 50 ), anthelmintic treatment ( 51 ), FMT ( 52 ), and alterations after intensive physical activity ( 53 ).…”
Section: Types Of Dysbiosis Indexesmentioning
confidence: 99%
“…This index achieved 74% sensitivity and 95% specificity for separation of healthy and CE dogs. Due to this good performance, numerous following studies utilized this index to quantify microbial dysbiosis for dogs or cats with CE ( 47 , 48 ), response to food ( 49 , 50 ), anthelmintic treatment ( 51 ), FMT ( 52 ), and alterations after intensive physical activity ( 53 ).…”
Section: Types Of Dysbiosis Indexesmentioning
confidence: 99%
“…Activity was associated with reduced alpha-diversity in the subgroup of dogs receiving glucosamine, according to Faith’s phylogenetic diversity. Previously, Tysnes et al ( 24 ) found that alpha-diversity in non-supplemented sled dogs did not differ pre- and post-race. Similar to our findings above, it was also found that age had an important role in changes in gut composition after exercise ( 24 ).…”
Section: Discussionmentioning
confidence: 89%
“…Sled dogs and other intensely exercising dogs frequently experience exercise-induced gastric disease (EIGD), characterized by gastric lesions and increased intestinal permeability ( 20–22 ). Recent work has provided evidence that exercise in racing sled dogs alters the microbiome, resulting in an increase in beneficial microbes and a concomitant decrease in dysbiosis-associated bacteria and supplementation of sled dogs with a targeted symbiotic altered the microbiome and decreased diarrhea, potentially due to a transient increase in Lactobacillaceae and Streptococcaceae and decreases in Clostridiaceae ( 23 , 24 ). However, the ability of dietary supplements to alter the microbiome is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As diarrhea is the leading cause of exercise discontinuation in exercising sled dogs ( 1 , 2 ), minimizing pathogenic microbes could have beneficial outcomes related to performance. For example, sled dogs running in a 400-km race in Norway presenting with low levels of dysbiosis-associated bacteria (i.e., Fusobacterium, Clostridium hiranonis , and Blautia ) prior to a race performed better than dogs with a greater level of these bacteria ( 48 ). As such, the fecal metabolite data in the current study suggest a shift toward an improved gut microbial environment.…”
Section: Discussionmentioning
confidence: 99%